2009
DOI: 10.1176/appi.ajp.2008.08020212
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-Specific Dissociation of Orbitofrontal Dysfunction in Boys With Pure Conduct Disorder During Reward and Ventrolateral Prefrontal Dysfunction in Boys With Pure ADHD During Sustained Attention

Abstract: The findings revealed a process-related dissociation of prefrontal dysfunction in ADHD and conduct disorder patients. Attention-related dysfunction in the ventrolateral prefrontal cortex was seen in ADHD patients, and reward-related dysfunction in the orbitofrontal cortex was seen in conduct disorder patients. These findings, together with the pattern of paralimbic dysfunction demonstrated among children with conduct disorder during sustained attention, support theories of abnormalities in orbitofrontal-parali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
236
2
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(275 citation statements)
references
References 44 publications
33
236
2
4
Order By: Relevance
“…This evidence suggests that high CU youth are more likely to initiate early, escalate, and/or persist in deviant behaviors because they are less mindful of its negative consequences [40][41][42][43][44]. T0 research has further shown that these deficits are neurally subserved by abnormalities in the "motivational network" (mesocorticolimbic dopamine pathways) that mediates reward-based decision-making [30,45]. Neuroimaging studies have related the decision-making impairment in CU youth to reduced representation of expected value within the ventromedial prefrontal cortex (how much reward/ punishment is associated with a response choice) and prediction error signaling within caudate (signaling the difference between the reward expected and that received) [39].…”
Section: Exemplar Phenotype: Callous-unemotional Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence suggests that high CU youth are more likely to initiate early, escalate, and/or persist in deviant behaviors because they are less mindful of its negative consequences [40][41][42][43][44]. T0 research has further shown that these deficits are neurally subserved by abnormalities in the "motivational network" (mesocorticolimbic dopamine pathways) that mediates reward-based decision-making [30,45]. Neuroimaging studies have related the decision-making impairment in CU youth to reduced representation of expected value within the ventromedial prefrontal cortex (how much reward/ punishment is associated with a response choice) and prediction error signaling within caudate (signaling the difference between the reward expected and that received) [39].…”
Section: Exemplar Phenotype: Callous-unemotional Traitsmentioning
confidence: 99%
“…Effective modes of communication are important to convey the need for the intervention to non-research audiences and to increase palatability to potential recipients, their families, funding agencies, and social systems, all of which may differ for addressing the needs of CU youth. Focusing on the preferences of consumers tends to translate more effectively into eventual behavior change [45].…”
Section: Exemplar Phenotype: Callous-unemotional Traitsmentioning
confidence: 99%
“…Rubia and colleagues [651] reported reduced orbitofrontal activation during a rewarded continuous performance task in adolescents with CD, whereas Bjork et al . [652] reported increased subgenual cortex activation in adolescents with externalizing disorders during a monetary incentive-delay task.…”
Section: Reviewmentioning
confidence: 99%
“…The inferior frontal cortex is known for its role in response inhibition 51 as well as sustained 52 or selective 53 attention, and impairment of these neurobehavioural functions may be related to the clinical features of ADHD. Interestingly, the large cluster differentiating the good and poor responders extended across the inferior frontal cortex and ventromedial prefrontal cortex, with the latter being implicated in emotion regulation, 18 reward and motivation, 21 or as part of the broader default mode network.…”
Section: Discussionmentioning
confidence: 99%